Formulating a Standardized Dental Record Format for Dental Surgeons in India - A Pilot Study on Dentists at Chennai and Ahmedabad - Selwin Gabriel Samuel; M B Aswath Narayanan; Dhwani Patel; Vennila Anand (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Dental record management remains to be a much unexplored arena in forensic odontology.While some developed countries have pre-set guidelines for their licensed dental surgeons to follow, Indialacks one such protocol. As a result, majority of dental surgeons in India do not maintain patients’ recordsproperly. This not only hampers the quality of dental practice, but also compromises its potential as avaluable forensic aid.Materials and Methods: This study is a descriptive cross-sectional study. A comprehensive case historyformat was drafted for dental record management by optimizing the protocols followed by some developedcountries. The protocols were supplied to 20 dental surgeons from Chennai and Ahmedabad, who werechosen by stratified simple random sampling. The dental surgeons were asked to follow the format for amonth and give detailed feedbacks thereafter, which were collected in feedback forms.Results: Out of 25 participants, only 15 of them completed the study. The feedback contained both positiveand negative comments, along with some with effective suggestions. As a collective opinion, the dentalsurgeons felt that the case history was too exhaustive. Though the dental surgeons unreservedly welcomedmost parts of it, some dentists had difficulties in adopting certain sections in their routine practice and rathersuggested removal or modification of those divisions.Conclusion: The feedbacks and suggestions given by the dentists clarified the feasibility of the prepareddental record format. However, further research on larger scales would be helpful in arriving at definiteconclusions.